2020
DOI: 10.3126/nmcj.v22i1-2.30031
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Fluoride concentration in drinking water of Kathmandu Valley

Abstract: Fluoride has a preventive effect on dental caries. However, excessive/insufficient ingestion of fluoride can lead to the development of dental fluorosis/increased risk for dental caries respectively. The objective of this study was to estimate fluoride concentration in drinking water of Kathmandu valley. It was a community based cross-sectional study in which drinking water samples were collected from municipal water supply and bottled water. Municipal water supply was collected according to eight water scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The result is in an agreement with the study done in Eastern Nepal , Kathmandu Valley and Dharan, Nepal by previous researchers. [20][21][22] A study done in the northern neighboring country China (Nepal-China border; Tibet) also revealed a similar finding of fluoride level in drinking water source. 23 This is in contrast to the southern neighboring country India, where the fluoride concentration is above the recommended level of WHO.…”
Section: Discussionmentioning
confidence: 57%
“…The result is in an agreement with the study done in Eastern Nepal , Kathmandu Valley and Dharan, Nepal by previous researchers. [20][21][22] A study done in the northern neighboring country China (Nepal-China border; Tibet) also revealed a similar finding of fluoride level in drinking water source. 23 This is in contrast to the southern neighboring country India, where the fluoride concentration is above the recommended level of WHO.…”
Section: Discussionmentioning
confidence: 57%
“…25,26 In most districts of Nepal including Kathmandu, the fluoride level in drinking water was found to be below the recommended optimum level whereas only one district had fluoride level exceeding 0.8 ppm (Parsa), and only 4% of the study population were exposed to the optimal level of fluoride in drinking water. 7,27 It is a common practice that the parents decide and purchases the needful It was evident with this review that the dental caries in both primary and the permanent dentition was prevalent in the children of Nepal in different ages. Dental caries in the primary dentition is a major public health problem particularly in developing and underdeveloped countries.…”
Section: Discussionmentioning
confidence: 91%
“…A study collected water samples from eight water distribution schemes in Kathmandu valley and showed that the fluoride level in the drinking water of Kathmandu Valley was below the permissible limit as recommended by WHO. 12 A study in the Eastern Developmental region of Nepal on water samples of different sources. Few regions in their study were having fluoride levels above 0.10 mg/L and the majority of the area had fluoride levels below 0.05 mg/L as recommended by WHO.…”
Section: Discussionmentioning
confidence: 99%
“…6 In Nepal, published studies have shown less fluoride content in the drinking water supply in Nepal. [11][12][13] Such a study has not been done in the Western part of Nepal.The aim of this study was to measure the mean concentration of fluoride in the drinking water of a municipality.…”
mentioning
confidence: 99%
See 1 more Smart Citation